Comparative Study of Grinding Machines Processes on Laboratory Scale and Production Scale in the Printing Ink Industry - Khanif Eko Prasetyo; I Dewa Gede Arsa Putrawan (Universitas Ahmad Dahlan, 2020)
Grinding is a common process in the ink industry. This process is required to achieve a particular particle size based on specifications. To achieve an optimal condition in grinding, exploration processes are needed. However, an exploration that commenced in the production scale will require a lot of energy and resources. This research objective is to build mathematical modeling and correlate processes of laboratory and production scale grinding. The modeled result which developed in a laboratory scale is expected to be implemented on a production scale, thus exploration processes can be commenced on a laboratory scale with minimal cost. Mathematical modeling is simulated in MatlabÂ®, while population balance is the bases of calculation. This research found that simulation can represent observation data. A correlation also formulated to predict the production scale grinding from laboratory scale evaluation.